Study on the Fate of the Carbopol® Polymer in the Use of Hand Sanitizer Gels: An Experimental Model to Monitor Its Physical State from Product Manufacturing up to the Final Hand Rinse - Marcello Marchetti; Alessandro Perini; Michela Zanella; Federico Benetti; Daniela Donelli (Microplastics)
Carbopol® is a typical jelly agent belonging to the family of cross-linked polyacrylic acid copolymers. It is largely used in antibacterial gels due to its self-wetting properties. In its pristine physical form, Carbopol® falls under the definition of microplastics, though significant changes could occur once added to hydroalcoholic solvents of the liquid formulations. To date, no life-cycle data regarding the physical state are available for this substance or for other similar polymers of the same chemical class. The aim of the present study was the investigation of the fate of Carbopol®-derived microplastics used in the formulation of typical hand sanitizer gels available in the Italian market, such as Amuchina® X-Germ, along the product life cycle. An experimental model was designed to detect the presence of Carbopol® microparticles from product manufacturing to the final use. FTIR and µ-FTIR were used to detect and characterize solid particles after the optimization of the sample preparation of different experimental matrices. While Carbopol® as such can be classified as a microplastic, in the commercial product, Carbopol® particles were not detected. Ten volunteers used the product according to the instructions reported on the label, and finally they rinsed their hands. Carbopol®-based particles were not detected in the water rinse, indicating that, after usage, the original form of the Carbopol microparticles was not retrieved. The study proposes, for the first time, a simple and comprehensive experimental approach to identify and characterize microplastics in finished products and along the life cycle by simulating their real-life usage. This approach could be also useful to evaluate the release of chemical components into the environment through the use of dermal products.